Lysozyme affects the microbial catabolism of free arginine in raw-milk hard cheeses. (August 2016) - D'Incecco, P.; Gatti, M.; Hogenboom, J.A.; Bottari, B.; Rosi, V.; Neviani, E.; Pellegrino, L.
Abstract: Lysozyme (LZ) is used in several cheese varieties to prevent late blowing which results from fermentation of lactate by Clostridium tyrobutyricum . Side effects of LZ on lactic acid bacteria population and free amino acid pattern were studied in 16 raw-milk hard cheeses produced in eight parallel cheese makings conducted at four different dairies using the same milk with (LZ+) or without (LZ-) addition of LZ. The LZ-cheeses were characterized by higher numbers of cultivable microbial population and lower amount of DNA arising from lysed bacterial cells with respect to LZ + cheeses. At both 9 and 16 months of ripening, Lactobacillus delbrueckii and Lactobacillus fermentum proved to be the species mostly affected by LZ. The total content of free amino acids indicated the proteolysis extent to be characteristic of the dairy, regardless to the presence of LZ. In contrast, the relative patterns showed the microbial degradation of arginine to be promoted in LZ + cheeses. The data demonstrated that the arginine-deiminase pathway was only partially adopted since citrulline represented the main product and only trace levels of ornithine were found. Differences in arginine degradation were considered for starter and non-starter lactic acid bacteria, at different cheese ripening stages. Highlights: Functionality of relevant LAB species in Grana Padano is not hindered by lysozyme. Lysozyme effect on the degradation of arginine has been evidenced for the first time. The arginine deiminase is still active in 16-mo ripened cheeses. Citrulline, not Ornithine, represents the main product of arginine degradation.